ICRF - volume charge - antenna edge interactions in the torsatrons U-3M and U-2M Part 2. VSC - RF antenna interaction - Berezhnyj, V.L. (Вопросы атомной науки и техники, 2016)
The influence of the electron emission and metal impurity emission from the antennas, including the U-3
torsatron antenna, on the RF-discharge has been analyzed. The both effects are the results of the antenna surface
bombarding with ions being accelerated in the self-consistent field of the volume-space charge (VSC). Проведен анализ влияния на ВЧ-разряд эмиссии электронов и металлических примесей из антенны, в
том числе из торсатрона У-3. Оба эффекта являются результатом бомбардировки поверхности антенны
ионами, ускоряющимися в самосогласованном поле объёмного пространственного заряда. Проведено аналіз впливу на ВЧ-розряд емісії електронів та металевих домішок з антени, у тому числі з
торсатрона У-3. Обидва ефекти є результатом бомбардування поверхні антени іонами, що прискорюються в
самоузгодженому полі об’ємного просторового заряду.